2021
DOI: 10.1210/clinem/dgab709
|View full text |Cite
|
Sign up to set email alerts
|

Extended Injection Intervals of Gonadotropins by Intradermal Administration in IVF Treatment

Abstract: Context Gonadotropins can be administered every five days under intradermal injection in in vitro fertilization (IVF) treatment. Objective To explore the effectiveness of intradermal injection of recombinant human FSH (rhFSH) for women undergoing IVF. Materials and Methods Women who received their first time IVF enrolled in this prospective intervention in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…In the era of increasing demand for more women, many with advanced age, with DOR/IOF request IVF treatments, different administration modes of rhFSH might optimize their response to COS. Our recent studies by administrating rhFSH in combination with PRP directly into the target ovarian tissue and also whole dimension subcortical ovarian administration indicated the restoration of ovarian function and clinical pregnancy in women with premature ovarian insufficiency and early menopause [ 15 , 16 ]. We have also demonstrated that both intradermally and intravaginally administered rhFSH can be absorbed efficiently and enhance ovarian follicle growth in POR women [ 17 , 19 , 29 , 30 , 31 ]. Thus, a personalized IVF treatment with fine-tuning of the Gn dose in accordance with each individual’s ovarian response has become a safe and effective practice [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the era of increasing demand for more women, many with advanced age, with DOR/IOF request IVF treatments, different administration modes of rhFSH might optimize their response to COS. Our recent studies by administrating rhFSH in combination with PRP directly into the target ovarian tissue and also whole dimension subcortical ovarian administration indicated the restoration of ovarian function and clinical pregnancy in women with premature ovarian insufficiency and early menopause [ 15 , 16 ]. We have also demonstrated that both intradermally and intravaginally administered rhFSH can be absorbed efficiently and enhance ovarian follicle growth in POR women [ 17 , 19 , 29 , 30 , 31 ]. Thus, a personalized IVF treatment with fine-tuning of the Gn dose in accordance with each individual’s ovarian response has become a safe and effective practice [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Double stimulation was employed immediately following the oocyte retrieval procedure in the operating room. The routine COS at our IVF unit is intermittent superficial subcutaneous/intradermal administration (the term intradermal administration will be used in the main article) of rhFSH [ 17 ]. The injection of Gn was performed on Days 2, 5, and 8 of the IVF cycle in accordance with our routine COS method [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations